Kinesiology taping: A Significant Potential for Stroke Patients with Hemiplegic Shoulder Pain - Rawal, Hardik; Lohar, Deepak; Aggarwal, Kapil; Khan, Jafar; Khan, Jafar; Menria, Shubham; Balala, Deepika; Rai, Richa Hirendra; pal, Renuka; Malvi, Ruchit; Jain, Rajshree (Journal of Neonatal Surgery, 2025)
Background: This study aims to assess the effectiveness of Kinesiology Taping therapy in managing hemiplegic shoulder pain and enhancing functional ability in stroke patients. It is hypothesized that the application of Kinesiology Taping will significantly reduce shoulder pain and contribute to better mobility and overall functional improvement in affected individuals. Methodology: This 12-month experimental study was conducted at the Department of Neurology, Pacific Medical University, Udaipur, with ethical approval (PMU/PMCH/IEC/2024/293). Sixty stroke patients (≥40 years) with hemiplegic shoulder pain and subluxation received kinesiology taping therapy (3 times/week, 30 min/session for 2.5 months). Pain and disability were assessed using VAS and SPADI. Informed consent and confidentiality were ensured. Results: Paired t-test analysis revealed a statistically significant improvement (p < 0.05) in shoulder pain and functional mobility among participants when comparing pre- and post-intervention scores. The results indicate a notable reduction in pain levels and enhanced functional ability following kinesiology taping therapy, confirming its effectiveness in managing hemiplegic shoulder pain in stroke patients. Conclusion: Kinesiology Taping Therapy helps reduce hemiplegic shoulder pain in stroke patients by improving proprioception, joint support, and muscle relaxation.